Analysis of shared common genetic risk between amyotrophic lateral sclerosis and epilepsy - Schijven, Dick; Stevelink, Remi; McCormack, Mark; van Rheenen, Wouter; Luykx, Jurjen J.; Koeleman, Bobby P. C.; Veldink, Jan H.; Weishaupt, Jochen H. (Neurobiology of aging, 2020)
Because hyper-excitability has been shown to be a shared pathophysiological mechanism, we used the latest and largest genome-wide studies in amyotrophic lateral sclerosis (n = 36,052) and epilepsy (n = 38,349) to determine genetic overlap between these conditions. First, we showed no significant genetic correlation, also when binned on minor allele frequency. Second, we confirmed the absence of polygenic overlap using genomic risk score analysis. Finally, we did not identify pleiotropic variants in meta-analyses of the 2 diseases. Our findings indicate that amyotrophic lateral sclerosis and epilepsy do not share common genetic risk, showing that hyper-excitability in both disorders has distinct origins.